Circulating CD8 T cells from patients with mild-to-moderate psoriasis are functionally impaired - Chen, Yiqiao; Tontini, Chiara; Tosi, Isabella; Barker, Jonathan N.; Di Meglio, Paola; Griffiths, Christopher E. M.; Bahri, Rajia; Bulfone-Paus, Silvia (Frontiers in Immunology, 2025)
BackgroundPsoriasis is a systemic, immune-mediated, inflammatory skin disease in which T cells have been found to play a significant role. The phenotypic and functional properties of circulating CD8 T cells in the pathogenesis of the disease are still ill-defined.ObjectiveThis study aimed to assess changes in the phenotype, activation status and mediator release of CD8 T cells in the peripheral blood of patients with mild-to-moderate psoriasis.MethodsPeripheral blood mononuclear cells from patients with mild-to-moderate psoriasis and healthy individuals were used to investigate the CD8 T cell immune phenotype and mediator release upon in vitro TCR-independent (phorbol 12-myristate 13-acetate (PMA) plus ionomycin (ION)) or TCR-dependent (anti-CD3/CD28) activation by flow cytometry.ResultsPatients with psoriasis exhibited reduced circulating CD8 memory T cell frequency compared to healthy controls. Additionally, although CD8 T cell subsets showed similar levels of the skin homing marker CCR4, they demonstrated a significant upregulation of B- and T-lymphocyte attenuator (BTLA) expression compared to healthy individuals. Upon CD8 T cell activation, IL-17A and IL-17F were expressed at low and comparable levels in psoriasis patients and healthy controls. In contrast, CD69, IFNγ, and Granzyme B were significantly decreased in anti-CD3/CD28-activated CD8 T cell subsets. PASI scores positively correlated with IFNγ-producing CD8 T memory cells and negatively with TNF-producing CD8- T cell subsets.ConclusionPatients with mild-to-moderate psoriasis showed a significant decrease in CD8 T memory cells and reduced release of cytotoxic mediators by CD8 T cells. Thus, this indicates that psoriasis impacts the functionality of circulating CD8 T cells.